Social indentification and corporate irresponsibility: A model of stakeholder punitive intentions - Antonetti, Paolo; Maklan, Stan (Wiley, 2016)
Scholars hypothesize that retaliations against corporate social irresponsibility (CSI) are more likely when observers share the social identity of the victims. We present a model that explains in-group bias against irresponsibility and identify collective narcissism as a moderator of this effect. Experiment 1 demonstrates that the effect of identity on retaliations is mediated by the perceived similarity of the victims which reinforces feelings of sympathy towards the victims and anger towards the corporation. These emotions drive stakeholders’ attitudes and retaliations. Our study shows that appraisals of the victims of CSI are an important antecedent of stakeholders’ emotions and behavioural intentions. Our evidence also demonstrates that sympathy, an emotion neglected by past research in this area, has a unique effect on individuals’ reactions. Experiment 2 demonstrates that social identity biases in individual punitive intentions are moderated by individuals’ level of collective narcissism. Collective narcissists see out-group victims as very dissimilar from the self, whereas individuals with low levels of collective narcissism do not differentiate between victims of CSI on the basis of their identity. We extend knowledge on stakeholders’ reactions to CSI and offer insights to organizations promoting campaigns against irresponsible behaviour or managing the fallout from cases of corporate irresponsibility.